Development of Android-Based Interactive Media Learning Economics Capital Market Materials - Wahid, Reza Nur; Cerya, Efni (Economic Education Analysis Journal, 2022)
This study aimed to produce an Android-based interactive media for economic learning in class X SMA/MA which was valid and practical. This type of research was Research and Development (R & D). The research was conducted at SMA N 1 Salimpaung for the 2020/2021 academic year. The test subjects involved in the research were media, language, material and evaluation validators, economics teachers and students. The model in this development used a 4-D model, namely definition, design, development, and dissemination, but this research was limited to the develop stage. The results of study obtained a score of 86.65%, from the material validator with a very decent category. The media validator obtained a score of 87.3%, with a very decent category. The assessment of the language validator got a score of 83% with a very decent category. Meanwhile, the evaluation validator got a score of 92% with a very decent category. The practicality results of the teacher obtained a score of 92.78% and the assessment of the students was 94.9%. The results of both assessments were in the very practical category. This android-based interactive media was declared very feasible to be applied to economics learning material for capital markets.